1992
DOI: 10.1002/jcp.1041520127
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hypoxia upon intracellular calcium concentration of human endothelial cells

Abstract: Ischemia is a situation occurring in several diseases including myocardial infarction and organ transplantation in which oxygenated blood supply is impaired. Ischemia leads to many cellular and tissue modifications, the most important one being cell death. Several explanations have been proposed to account for these modifications and cell death; among them is calcium overload. However, the influence of calcium concentration on the alteration of endothelial cell functions or viability during ischemia are still … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
55
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 131 publications
(60 citation statements)
references
References 33 publications
5
55
0
Order By: Relevance
“…Previous studies have shown that exposure of ECs to hypoxia results in an elevation in intracellular calcium (28). In view of the association of increased cytosolic calcium with EC WP exocytosis in response to thrombin or histamine (29, 30), we considered whether exposure of ECs to hypoxia could initiate this process.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that exposure of ECs to hypoxia results in an elevation in intracellular calcium (28). In view of the association of increased cytosolic calcium with EC WP exocytosis in response to thrombin or histamine (29, 30), we considered whether exposure of ECs to hypoxia could initiate this process.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, it is less likely that phosphorylation of HDAC7 plays a role in translocation of HDAC7 under hypoxia. Because hypoxia causes an increase in intracellular calcium concentration in epithelial cells (42), hypoxia-induced phosphorylation of HDAC7 might be involved in stabilization of HIF-1␣⅐HDAC7 complex or export of HIF-1␣ from the nucleus to the cytoplasm.…”
Section: Discussionmentioning
confidence: 99%
“…While EDRF synthesis is stimulated by high pH buffer through a mechanism dependent on Ca2" influx (Mitchell, de Nucci, Warner & Vane, 1991), decreases in extracellular pH could theoretically promote metabolic vasodilatation by prolonging its biological half-life (Ignarro, 1989). It remains controversial whether EDRF contributes to hypoxic vasodilatation, although hypoxia elevates [Ca2"]i in cultured endothelial cells which could potentially activate eNOS (Arnould, Michiels, Alexandre & Remacle, 1992).…”
Section: Hyperaemiasmentioning
confidence: 99%